Drug Use Status in Youth: The Role of Gender and Delay Discounting. (24th August 2017) - Thamotharan, Sneha; Hahn, Hunter; Fields, Sherecce
ABSTRACT: Background: Evidence from gender and delay discounting studies suggests these variables may influence drug use in youth. However, no studies to date have examined sexual discounting with regard to drug use in youth. Objectives: The present study examined gender and delay discounting, both monetary and sexual, with regard to the drug use status of alcohol, tobacco, and marijuana. Methods: Youth aged 14–21 years ( n = 155) provided demographic and drug use information and completed behavioral tasks assessing monetary and sexual discounting in a single laboratory session. Chi-square and analysis of variance were used to assess group differences. Results: Across drug use status, differences in gender and sexual discounting but not monetary discounting were found. Moderate drinkers and smokers were more likely to be male and displayed steeper sexual discounting rates. However, no interaction effect between gender and discounting differences on drug use status was observed. Conclusions: Findings suggest that drug use may manifest differently by gender and highlight the domain specificity of sexual discounting. These findings further highlight the need to incorporate gender and domain-specific discounting measures when investigating drug use pathology and interventions in youth.